General practitioners' attitudes towards and frequency of collaboration with pharmacists in China: a cross-sectional study - Songtao Cai; Xianghui Huang; Connie Van; Wanchao Li; Ming Yan; Yiting Lu; Haixin Li; Zhiling Deng; Panpan Lu; Zhijie Xu (BMC, 2023)
Abstract Background Building interprofessional working relationships between general practitioners (GPs) and pharmacists is essential to ensure high-quality patient care. However, there is limited Chinese literature on GP-pharmacist collaboration, and few studies have explored GPs' experiences with pharmacist integration into general practices. This study aimed to investigate GPs' attitudes towards and frequency of collaboration with pharmacists in China. Methods This cross-sectional study used an online self-administered questionnaire integrating two scales, ATCI-GP and FICI-GP, which had been translated and validated to investigate 3,248 GPs from February 15 to March 15, 2023 across Zhejiang Province, China. Descriptive analyses were used, and the factors associated with GPs' frequency of collaboration with pharmacists were explored using logistic regression analysis. Results A total of 2,487 GPs (76.6%) responded and consented to participate in the survey; 52.3% were male and the mean age was 35.4 years. Most GPs agreed that they shared common goals and objectives with pharmacists when caring for patients (90.0%), and pharmacists were open to working with them on patients' medication management (80.8%). However, half of the GPs did not change or seldom changed the patient's medication on the pharmacist's advice (51.4%). Logistic regression analysis showed that GPs who were older and had more years of practice were more likely to agree that pharmacists were willing to collaborate, had common goals for treatment and that they would change the patient's medication on the advice of the pharmacist. GPs who had regular communication protocols (adjusted odds ratio1 [aOR1] = 1.88, 95% CI 1.45-2.45; aOR2 = 3.33, 95% CI 2.76-4.02), participated in joint continuing education (aOR1 = 1.87, 95% CI 1.44-2.43; aOR2 = 2.27, 95% CI 1.91-2.70), provided recommendations for medication review (aOR1 = 3.01, 95% CI 2.07-4.38; aOR2 = 3.50, 95% CI 2.51-4.86), and communicated with pharmacists during resident training (aOR1 = 2.15, 95% CI 1.78-2.60; aOR2 = 1.38, 95% CI 1.18-1.62) were associated with a more positive attitude towards and higher frequency of cooperation. Conclusions GPs in China displayed a positive attitude towards cooperating with pharmacists, but they did not demonstrate a similar level of practice. As environmental determinants impact interdisciplinary collaboration, healthcare managers and policy-makers need to implement measures that foster a supportive environment conducive to interdisciplinary collaboration.